CONTRIBUTIONS BY RASHTIRYA SEVA SANGH IN NATION BUILDING - Satish L Chaple (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Rashtriya Swayamsevak Sangh (RSS) has significantly contributed to social harmony by fostering unity across communities and promoting the philosophy of Vasudhaiva Kutumbakam. Through the formation of Ekal Vidyalayas, it has provided education to children in rural and tribal areas, ensuring inclusive learning opportunities. The organization has also established hospitals and healthcare initiatives to serve underprivileged communities, improving access to medical care. Additionally, through Lok Kalyan programs, the RSS has undertaken various welfare activities, including disaster relief, skill development, and empowerment programs for marginalized groups.